Local and global pollution and international environmental agreements in a network approach - Michael Günther; Tim Hellmann (Bielefeld University, Center for Mathematical Economics (IMW), 2015)
Increasing concerns about climate change have given rise to the formation of International Environmental Agreements (IEAs) as a possible solution to limit global pollution effects. In this paper, we study the stability of IEAs in a repeated game framework where we restrict to strategies which are simple and invariant to renegotiation. Our main contribution to the literature on IEAs is that we allow for heterogeneous patterns of pollution such that additional to a global effect of pollution there are local pollution effects represented by a network structure. We show that stable IEAs exist if the network structure is balanced. Too large asymmetries in the degree of local spillovers may however lead to non-existence of stable structures. The generality of our approach allows for several applications to general problems in the provision of public goods.
urn:nbn:de:0070-pub-27722901
Keywords: C72; C73; D85; F53; Q54; 330; Coalition structures; Networks; International environmental agreements; Weak renegotiation-proofness